A General Solution for Troesch's Problem. (27th November 2012) - Vazquez-Leal, Hector; Khan, Yasir; Fernández-Anaya, Guillermo; Herrera-May, Agustín; Sarmiento-Reyes, Arturo; Filobello-Nino, Uriel; Jimenez-Fernández, Víctor-M.; Pereyra-Díaz, Domitilo
Abstract : The homotopy perturbation method (HPM) is employed to obtain an approximate solution for the nonlinear differential equation which describes Troesch's problem. In contrast to other reported solutions obtained by using variational iteration method, decomposition method approximation, homotopy analysis method, Laplace transform decomposition method, and HPM method, the proposed solution shows the highest degree of accuracy in the results for a remarkable wide range of values of Troesch's parameter.